2017
DOI: 10.3390/jfb8030032
|View full text |Cite
|
Sign up to set email alerts
|

Potential New Non-Invasive Therapy Using Artificial Oxygen Carriers for Pre-Eclampsia

Abstract: The molecular mechanisms of pre-eclampsia are being increasingly clarified in animals and humans. With the uncovering of these mechanisms, preventive therapy strategies using chronic infusion of adrenomedullin, vascular endothelial growth factor-121 (VEGF-121), losartan, and sildenafil have been proposed to block narrow spiral artery formation in the placenta by suppressing related possible factors for pre-eclampsia. However, although such preventive treatments have been partly successful, they have failed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Labyrinth volume reduction was driven by a reduction in fetal capillaries at histological level and coincided with the reduction in fetoplacental vessel volume on microcomputed tomography. Although this is the first published experience using this technique in the rabbit, labyrinth alterations have been previously described in several other FGR models, including those induced by maternal undernutrition 35,36 , exogenous 37,38 and endogenous 39 glucocorticoid excess, heavy metal exposure 40 , NO synthetase inhibition 41,42 , and systemic inflammation 43 . Furthermore, labyrinth underdevelopment, and particularly fetal vessel reduction, has www.nature.com/scientificreports/ been associated with reduced levels of different placental vascular endothelial growth factor (VEGF) mRNAs 38 , and glucose transport capacity 39,44 .…”
Section: Discussionmentioning
confidence: 91%
“…Labyrinth volume reduction was driven by a reduction in fetal capillaries at histological level and coincided with the reduction in fetoplacental vessel volume on microcomputed tomography. Although this is the first published experience using this technique in the rabbit, labyrinth alterations have been previously described in several other FGR models, including those induced by maternal undernutrition 35,36 , exogenous 37,38 and endogenous 39 glucocorticoid excess, heavy metal exposure 40 , NO synthetase inhibition 41,42 , and systemic inflammation 43 . Furthermore, labyrinth underdevelopment, and particularly fetal vessel reduction, has www.nature.com/scientificreports/ been associated with reduced levels of different placental vascular endothelial growth factor (VEGF) mRNAs 38 , and glucose transport capacity 39,44 .…”
Section: Discussionmentioning
confidence: 91%
“…HbV, which is a type of Nano-HBOC with a nanoscale size and no blood group antigens, can pass through narrow placental spiral arteries and capillaries to provide an efficient O 2 supply to the placenta [ 247 , 248 ]. Ohta et al [ 249 ] intravenously injected HbV into a rat preeclampsia model. The results showed that HbV alleviated fetal hypoxia by supplying oxygen while improving fetal growth restriction in a murine model of preeclamptic pregnancy.…”
Section: Nano-hbocs For Other Biomedical Applicationsmentioning
confidence: 99%
“…AOC products are feasible in traumatic conditions as well as in austere environments where blood donation is impossible. In addition, these may be used in medical treatments such as elective and cardiovascular surgeries (Spahn 2018 ; Haldar et al 2019 ); they are effective in alleviating ischemic conditions such as cerebral hypoxia (Kaneda et al 2014 ) and fetal ischemia (Ohta et al 2017 ). In addition, they are non-perishable, stable to supply, and economically feasible (Bialas et al 2019 ).…”
Section: Aocs and Their Benefitsmentioning
confidence: 99%